Investigations of bisacodyl with modified β-cyclodextrins: Characterization, molecular modeling, and effect of PEG. (10th December 2015) - Li, Shanshan; Wang, Lili; Jiang, Jian; Tang, Peixiao; Wang, Qing; Wu, Di; Li, Hui
Highlights: Binary and ternary complexes of BS with DM-β-CD/HP-β-CD using PEG were prepared. The encapsulation modes calculated were coincident with experimental data. Solubility, dissolution and bioavailability of BS were improved by wrapping in CDs. Addition of PEG enhanced inclusion ability and improved properties of BS slightly more. Abstract: Bisacodyl inclusion into hydroxypropyl-β-cyclodextrin and 2, 6-di- O -methyl-β-cyclodextrin cavities was experimentally and theoretically investigated, and the effect of PEG 4000 on these inclusions was studied. Isothermal calorimetry titration curves indicated that the binary inclusion processes are enthalpy- and entropy-driven. The solid-state complexes were fully characterized by FT-IR, XRPD, DSC and SEM analyses. FT-IR, 1 H NMR, and ROESY studies provided the most favorable encapsulation modes of binary complexes, and results were further confirmed by molecular docking and molecular dynamics studies. The presence of PEG 4000 slightly enhanced encapsulation efficiency, solubility and dissolution rates of the binary complexes. In vivo studies showed that complexes with CDs markedly accelerated gastrointestinal transit time compared with pure bisacodyl, whereas addition of PEG 4000 showed no further significant improvement of the bioavailability.